Cancel Culture and the Reconfiguration of Public Legitimacy in Indonesia’s Digital Public Sphere - Rabathy, Qisthy; Nurdiantara, Robby Rachman (Khazanah Sosial, 2026)
Abstract This study aims to examine how cancel culture operates as a structured mechanism of digital power that produces material consequences within Indonesia’s creative industry, using the controversy surrounding actor Abidzar Al Ghifari in the Indonesian adaptation of A Business Proposal as a study. The urgency of this research lies in a significant gap in the literature, which predominantly frames cancel culture as a psychological or moral phenomenon without systematically mapping its power relations, operational patterns, and economic impacts within networked publics. This study employs a qualitative approach using a virtual ethnography design. Data were collected from 300 primary posts on the X platform between January and March 2025, supplemented by interaction metrics. The findings demonstrate that cancel culture in the Abidzar case unfolded through five operational stages: the triggering controversial statement, narrative diffusion through fandom and anonymous accounts, public opinion consolidation dominated by professionalism criticism (53.67%), collective action in the form of boycott calls (9.67%), and discursive normalization within digital memory. The accumulation of interactions reached 57.5 million views, 523,274 likes, and 95,028 retweets, indicating the dominance of propagative rather than deliberative communication patterns. This digital public opinion hegemony translated into tangible economic consequences, including a reduction in cinema screens from 1,270 to 551 and a decline in the IMDb rating to 1/10. The study argues that digital participation can transform symbolic capital into measurable economic outcomes through algorithmic amplification. Theoretically, this research contributes by formulating an operational cycle of cancel culture and demonstrating the integration of capillary power relations, algorithmic mediation, and symbolic capital struggles within the digital public sphere. Practically, it recommends strengthening platform moderation policies, developing algorithmic literacy–based crisis communication systems, and promoting critical digital literacy programs. The originality of this study lies in its empirical demonstration of the conversion of symbolic power into commercial failure within Indonesia’s creative industry.